A musical view of the universe : Kalapalo myth and ritual performances - Basso, Ellen B., 1942- (University of Pennsylvania publications in conduct and communication., 1985)
A Musical View of the Universe is a study of the relationships between spoken myth and musical ritual in a native Brazilian community, the Carib-speaking Kalpalo of the Upper Xingu Basin. The book focuses on the meanings created and expressed through performance of artistic processes in which sound symbols provide a unifying interpretive matrix. Through sound symbols, Kalpalo ideas about types of beings, their relationships, and activities of mind are conceived, represented, and rendered apparent. The book includes the first collection of South American Indian narratives translated directly from the original language from taped performances. Ellen B. Basso's translations take into account the interaction among participants in the storytelling situation and the qualities of narrative performance that result.